Muticomponent Melt-Electrowritten Vascular Graft to Mimic and Guide Regeneration of Small Diameter Blood Vessels - Hoey, David; Kelly, Daniel (My University, 2024)
Cardiovascular disease is a leading cause of morbidity. Current treatments include vessel substitution using autologous/synthetic vascular grafts, but these commonly fail in small diameter applications, largely due to compliance mismatch and clot formation. In this study, a multicomponent vascular graft, that takes inspiration from native vessel architecture, is developed to overcome these limitations. Melt electrowriting (MEW) is used to produce tubular scaffolds with vascular-mimetic fiber architecture and mechanics, which is combined with a lyophilized fibrinogen matrix with tailored degradation kinetics to generate a hybrid graft. The MEW framework not only contributes to graft mechanics, but also provides contact guidance to direct cell/neotissue orientation and mimic the native tunica media. This construct is further functionalized with heparin, which in combination with the smooth extracellular matrix (ECM) surface, reduced platelet adhesion and clot formation providing a substrate for endothelization, thereby mimicking the function of the intima. Lastly, an outer electrospun layer representing the adventitia is added to improve elasticity and reduce permeability. This graft satisfies ISO implantability requirements, matches the compliance of native vessels, and reestablishes physiological flow with minimal clot formation in a preclinical model. Therefore, this graft represents an innovative off-the-shelf alternative to address the unmet clinical need for small-diameter vascular grafts.
PUBLISHED